SEX EDUCATION AMONG HIGH SCHOOL STUDENTS- A NEED ANALYSIS - Joy, Anjana (PEOPLE: International Journal of Social Sciences, 2018)
Aim: To Study the Need of Sex Education among High School students. Objectives: To study the knowledge about sexuality among students and to study the attitude of students towards introducing sex education in schools. Method: Self made questionnaire was used for collecting data. Result: As compared to females, males have more knowledge about sex and sexuality. Males show more positive attitude towards sex education.14.4% students gave first preference for teacher for getting advice about sexual health, 54.4% students gave first preference for mother, 7.8% students gave first preference for father, 11.7 % students gave first preference for friends, 4.4 % gave first preference for doctor, 3.3 % gave first preference for counselor and 3.9 % gave first preference for elder siblings. More students prefer to get advice from their mother. Family has a prominent role in imparting sex education. Providing proper sex education helps the women to maintain a good sexual health, helps the male to maintain a good relation with the opposite gender, helps in reducing crimes related to child abuse, women abuse etc. Even the social issues like child marriage, women abuse etc can be controlled by providing proper sex education which can help the people to lead a peaceful life with proper social relations.